Serum orexin-A (OXA) level decreases in polycystic ovarian syndrome - Yilmaz, Ercan; Celik, Onder; Celik, Nilufer; Simsek, Yavuz; Celik, Ebru; Yildirim, Engin (Gynecological endocrinology, 2013)
Abstract Aim: In the current study, we aimed to investigate whether serum orexin-A (OXA) levels are different in polycystic ovary syndrome (PCOS) subjects. Materials and methods: Thirty-six women with PCOS and 40 healthy, age and body mass index-matched controls were included in the prospective cross-sectional study. All subjects underwent venous blood draws during the early follicular phase after overnight fasting. Serum OXA levels were measured with an enzyme immunoassay (EIA). The relationships between the serum OXA levels and the anthropometric and metabolic parameters were also assessed. Results: The serum OXA levels were lower in the women with PCOS compared to the control group. The serum OXA levels were correlated negatively with systolic blood pressure, the Ferriman-Gallway score and LH and free testosterone levels. Conclusion: Our results indicate that serum OXA levels decrease in the serum of women with PCOS.